Correlation Between Disease Stage and the Presence of Viable Circulating Tumor Cells in Endometrial Cancer - Kiss, Imrich; Kolostova, Katarina; Matkowski, Rafał; Jędryka, Marcin; Czekański, Andrzej; Pavlasek, Jiri; Bobek, Vladimir (Anticancer research, 2018)
BACKGROUND/AIM: The presence of circulating tumor cells (CTCs) in the peripheral blood of patients with solid tumors is associated with a poor prognosis. However, there are limited data concerning the detection of CTCs in endometrial cancer (EC). The aim of this study was to evaluate the presence of CTCs in the peripheral blood of patients with EC. MATERIALS AND METHODS: Peripheral blood samples from 92 patients who underwent a surgical procedure were evaluated using MetaCell® separation technology for CTCs. RESULTS: CTCs were detected in 69 (75%) patients with EC. CONCLUSION: CTCs were detected in a higher percentage of patients than in other studies. The results showed that the technology applied in this study can efficiently capture viable tumor cells in the blood that can be cultured while maintaining their original phenotype. This paper discusses the first successful culturing of human circulating endometrial cancer cells for further downstream functional and molecular characterization.
Keywords: nádory endometria; Endometrial Neoplasms; lidé; nádorové cirkulující buňky; Female; circulating tumor cells; culturing; staging nádorů; endometrial cancer; Neoplastic Cells, Circulating; Neoplasm Staging; CTCs; ženské pohlaví; Humans